Path Planning of Autonomous Agricultural Vehicles - Nepal, Rituraj (My University, 2020)
Autonomy in the automotive industry is not a new concept. Advanced changes in technology have made it possible. With this trend, bringing autonomy to industrial agricultural fields in this era is also possible. With the ever-increasing food demand in this growing population, autonomy in farming is also a requirement. Major historical agricultural methods such as conventional and conservational agriculture are discussed. They no longer serve the purpose of bringing sustainability to the environment which gave to our findings of applying precision agriculture for the next generation agricultural methodology. One of the factors of precision agriculture is the utilization of robots. There are, however, major challenges in planning paths during different processes. Path planning is not only connected to the precision level of sensors and actuators but also on how software is deployed and the type of algorithm designed. Therefore, the procedural steps are discussed. We found that classification of agricultural fields with respect to geometrical shapes would be one of the first steps in solving it. Defining various geometri- cal indices, fields in various parts of the world can be classified. Depending on the diversity in the field shape, algorithms are developed that would be robust and required steps are planned. In this process, there are relatively good tactics of cost optimization which bring to using simulation tools. They are used to design and test robots and environments where robots are supposed to be deployed. It not only does optimization but brings ease and considerable certainty in the real process. The challenge again is selecting the right tools for individual needs. Thus, various simulation tools are discussed and compared. Analysis of challenges to bring agricultural autonomy in action are also presented. Many research papers are summarized, combined, and compiled to present an ordered way of bringing autonomy to agriculture.
Keywords: robotics, path planning, simulation, agricultural autonomy